Approaches to SARS-CoV-2 and other vaccinations in children with a history of multisystem inflammatory syndrome (MIS-C): An international survey - Minoia, Francesca; Lucioni, Federica; Heshin-Bekenstein, Merav; Vastert, Sebastiaan; Kessel, Christoph; Uziel, Yosef; Lamot, Lovro; Ruperto, Nicolino; Gattorno, Marco; Bracaglia, Claudia; Toplak, Natasa (Frontiers in Pediatrics, 2022)
Background. Following the Coronavirus Disease-19 (COVID-19) pandemic outbreaks, the hyperinflammatory condition termed Multisystem Inflammatory Syndrome in Children (MIS-C) became a healthcare issue, worldwide. Since December 2020 the mRNA vaccine against SARS-CoV-2 has become available with a good safety profile. However, evidence regarding safety and vaccination strategies in children with previous MIS-C is still lacking. The aim of our study was to investigate the current approach of international centers to anti-SARS-CoV-2 and other vaccinations in children with a history of MIS-C. Methods. Physicians who care for patients with MIS-C were invited to anonymously complete a 15-question, web-based survey. The survey was open from October 6 to December 31, 2021. Results. A total of 290 replies from 236 centers in 61 countries were collected. Most respondents (86%) were pediatric rheumatologists. The anti-SARS-CoV-2 vaccine was available in 85% of the countries. Sixty-seven centers (28%) in 22 countries already vaccinated MIS-C patients without adverse reactions in most cases (89%). Six reported complications: 2 not specified, 3 mild symptoms and 1 reported a MIS-C-like reaction. Most centers (84%) favored vaccinating MIS-C patients against SARS-CoV-2, after 3-6 months (40%), 6-12 months (52%) or > 12 months (8%). The survey revealed broad heterogeneity of responses among healthcare providers within the same country and within the same center. The variable with the greatest impact on the decision not to vaccinate MIS-C patients was the current lack of evidence (51%), followed by patient/parent objection (40%). The most relevant parameters in the vaccination strategy were time from MIS-C episode (78%), immunosuppressive treatment (35%), SARS-CoV-2 serologic status (32%), and MIS-C features (31%). Almost all centers favored continuing regular vaccination with non-live (99%) and live (93%) vaccines; however, with high variability in suggested timelines. Conclusion. To date, the experience of the international pediatric rheumatology community in vaccinating MIS-C patients against SARS-CoV-2 is overall reassuring. However, lack of evidence causes broad heterogeneity in vaccination strategy worldwide.